A Retrospective Analysis Comparing Post‐Operative Bleeding with Various Doses of Aspirin after Lower Extremity Joint Arthroplasty or Revision. Issue 7 (18th June 2021) - Watts, Paula J.; Kopstein, Michael; Harkness, Weston; Cornett, Brendon; Dziadkowiec, Oliwier; Jenkins, Patrick; Hicks, Mary E.; Hassan, Shakib; Scherbak, Dmitriy
Abstract: Study Objective: Previous studies have shown that aspirin is noninferior to other anticoagulation therapies in preventing postoperative venous thromboembolism following lower extremity arthroplasty or revision; however, its optimal dosing for this indication is less clear. This study aims to compare the odds of bleeding between different aspirin dosages following lower extremity joint arthroplasty or revision. Design: This is a 3‐year retrospective multi‐center cohort study across the United States and its territories. Setting: This study included patients admitted for total hip or knee arthroplasty or revision and were treated with prophylactic aspirin. Patients, Intervention, Measurements: Patients were assigned to groups based on a total daily aspirin dose of 81, 162, 325, or 650 mg. Data were analyzed for postsurgical bleeding and thromboembolism events occurring during the initial admission and up to 40 days following surgery. Other exploratory variables included type of surgery, hip or knee arthroplasty, length of stay, and patient demographic data. Main Results: Among 53, 848 patients receiving aspirin, 3922 received a total daily dose of 81 mg, 19, 341 received a total daily dose of 162 mg, 5256 received a total daily dose of 325 mg, and 25, 329 received a total daily dose of 650 mg. Bleeding occurred in 466 (0.87%) patients and venous thromboembolism (VTE) in 209 patients (0.39%). The odds of bleeding were compared using logistic regression, with the 650‐mg dose as the reference group. None were statistically significant for bleeding between all studied aspirin doses: 81 mg (OR 1.12, 95% CI 0.83–1.51, p = 0.451), 162 mg (OR 0.83, 95% CI 0.67–1.03, p = 0.097), and 325 mg (OR 0.83, 95% CI 0.59–1.13, p = 0.245). The odds of VTE were also not statistically significant: 81 mg (OR 0.71, 95% CI 0.40–1.17, p = 0.181), 162 mg (OR 0.75 95% CI 0.54–1.03, p = 0.072), and 325 mg (OR 1.00, 95% CI 0.64–1.53, p = 0.989). Conclusions: There were no significant differences in the odds of bleeding or venous thromboembolism among all studied aspirin dosages in patients receiving aspirin for thromboprophylaxis following lower extremity joint arthroplasty or revision.